Exploring Language Acquisition Development in the Second Cycle of Education in Venezuela: Challenges and Opportunities - Marisa Guenardo Velix; Carlos Fenandes; Cosmo Brito Monteoro; Barbara Arbaiza; Wang, Huang Yen (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study examines language acquisition in Venezuela's second cycle of education, a critical stage for students aged 12 to 15 as they solidify their proficiency in Spanish and begin to expand their skills in English. This research is vital as it investigates how these methods prepare students for secondary education and a globalized world. The qualitative study involved semi-structured interviews, focus groups, and classroom observations with teachers, administrators, and students to understand the effectiveness of current teaching practices and the challenges faced. The findings reveal a blend of traditional and modern teaching methods in Venezuelan classrooms, particularly the integration of direct instruction and grammar drills with communicative language teaching (CLT). This combination was effective in addressing diverse student needs, particularly in developing strong Spanish language skills. However, the variability in English language proficiency highlighted significant challenges, particularly related to resource limitations and socio-economic disparities. Teachers reported that while traditional methods provided a strong linguistic foundation, the effectiveness of CLT was often hindered by external factors such as inadequate resources and varying levels of student exposure to English outside of school. The study's conclusions emphasize the need for broader educational reforms to address these systemic issues, particularly the need for updated resources, greater access to technology, and enhanced professional development for teachers. The research suggests that while current methodologies are sound, their effectiveness is limited by external constraints. To better prepare students for the globalized world, these challenges must be addressed. Future studies should focus on exploring the impact of socio-economic factors on language acquisition outcomes and the effectiveness of integrating technology in language instruction.